Indonesia Darurat Kekerasan pada Anak, Edukasi Kekerasan Perlu Dilakukan sebagai Pencegahan Dini - Prima Sihombing; Berlianti, Berlianti (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
Violence seems to have become a culture for society, because many people assume that violence is an alternative to solving problems. At some times, one person can be a victim of violence, but at other times can also be a perpetrator of violence. But one thing is certain, the weak are the victims, and the child is the most vulnerable victim to this situation. Therefore, children must be protected and all parties must play an active role in it. And educating children about violence is one way to prevent early violence against children. Prevention are necessary in order for children to know whether they are getting violence or not, so that they know what they will do next. This devotion is performd at the Cinta Kasih Social Welfare Institute for Children in Medan Sunggal with more than 40 educated children. By doing this devotion, students hope that children at the Cinta Kasih Social Welfare Institute for Children can protect themselves and pay more attention to violence around them.